An Innovative Approach to Education in the Context of Sustainable Development; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 26 : Responsible Research and Innovation (RRI 2016) - Burmistrova N. A. Nataliya; Kormiltseva E. A. Elena; Shmakova A. P. Alexandra; Loshchilova M. A. Marina Andreevna (2017, 2017)
Title screen